PENDIDIKAN AKHLAK DALAM LINGKUNGAN KELUARGA MENURUT IMAM ABU LAITS AS-SAMARQANDI - Bakri, Maskuri; Hayati, Ihda Nur; Alaudin, Muhammad Khanif (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam Universitas Islam Malang, 2022)
The problems that occur in the educational environment are increasingly diverse and this does not only come from the environment of people who have less education, even in the education of someone who is considered to be qualified, there are still problems that should no longer be done. This has a negative effect on the development and success of the world of education. Whereas the main support for progress in the industrial era 4.0 is education. By having the next generation of the nation who has perfect morals and education, and is willing to practice it, this is what can ensure the progress of the nation morally and in action. Imam Abu Laits is a prominent cleric in the Ummayyah dynasty who gives his thoughts through works that are considered familiar in the world of Indonesian salafy education. Using qualitative research methods by deepening the problem through library research, a literature review conducted by researchers. By gathering all the information contained in the documentation of the book, Imam Abu Laits's views on moral education in the family environment are as follows; (1) The rights of parents, (2) maintain friendship, keep yourself from lying. In this article the author tries to describe the explanations and opinions of Imam Abu Laits about moral education in the family environment.Keywords: Moral education, family environment, Imam Abu Laits.Abstrak Â Permasalahan yang terjadi dalam lingkungan pendidikan semakin bermacam-macam dan hal tersebut tidak hanya keluar dari lingkungan orang yang pendidikannya kurang, bahkan dalam pendidikan seseorang yang dianggap sudah mumpuni masih saja terdapat permaslahan yang semestinya sudah tidak lagi dilakukan. Hal tersebut memberikan efek yang buruk dalam pengembangan dan keberhasilan dunia pendidikan. Padahal penopang utama dalam kemajuan di era indutri 4.0 adalah pendidikan. Dengan memiliki generasi penerus bangsa yang memiliki akhlak dan pendidikan yang sempurna, serta mau untuk mengamalkannya maka hal tersebut lah yang dapat menjamin kemajuan bangsa secara moral dan tindakan. Imam Abu Laits merupakan tokoh ulama pada dinasti Ummayyah yang memeberikan pemikirannya melalui karya yang sudah di anggap tidak asing di dunia pendidikan salafy Indonesia. Menggunakan metode penelitian kualitatif dengan melakukan pendalaman masalah melalui library research kajian pustaka yang dilakukan oleh peneliti. Dengan menghimpun segala informasi yang terkandung dalam dokumentasi kitab menghasilkan beberapa pandangan Imam Abu Laits dalam pendidikan akhlak dalam lingkungan keluarga, adalah sebagai berikut; (1) Hak orang tua, (2) menjaga silaturrahmi, menjada diri dari bohong. Pada artikel ini penulis mencoba untuk menguraikan penjelasan dan pendapat Imam Abu Laits tentang pendidikan akhlak dalam lingkungan keluarga.Kata Kunci: Pendidikan akhlak, lingkungan keluarga, Imam Abu Laits